Joint Electricity and Heat Production Possibilities on the Basis of the District Trigeneration Plant; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Ershov V. Vadim (2016, 2016)
Title screen